Violent street crime versus harmful white-collar crime: a comparison of perceived seriousness and punitiveness - Michel, Cedric (Critical criminology, 2016)
Recent studies have challenged traditional wisdom regarding public apathy about white-collar crime by revealing equal or greater perceived seriousness of these offenses among respondents relative to traditional crime. Nevertheless, subjects in those studies were generally asked to contrast white-collar crime scenarios with a non-violent street crime baseline vignette. Perhaps a violent street crime would have invited lower perceived seriousness for the white-collar offenses. Participants in the present study were asked to (1) read vignettes describing violent street crimes and physically harmful white-collar crimes, (2) compare their seriousness, and (3) determine appropriate sanctions. Subjects perceived the violent crime scenarios presented to them to be more serious than the harmful white-collar crime vignettes. Further, they were less punitive toward white-collar offenders compared with street criminals. Implications of these findings are discussed.